Ginsenoside-Rg3 inhibits the proliferation and invasion of hepatoma carcinoma cells via regulating long non-coding RNA HOX antisense intergenic. Issue 1 (1st January 2021) - Pu, Zhongjian; Ge, Fei; Wang, Yajun; Jiang, Ziyu; Zhu, Shilin; Qin, Shukui; Dai, Qijun; Liu, Hua; Hua, Haiqing
ABSTRACT: Ginsenoside Rg3, a natural compound, has been reported to function as an anticancer agent for hepatoma carcinoma, while the mechanisms underlying the anticancer effects are not clear. Therefore, the objective of our study was to explore the impact of RG3 on cell migration and invasion by regulating the lncRNA HOX antisense intergenic (HOTAIR) expression involving PI3K/AKT signaling pathway. qRT-PCR was utilized to measure the mRNA expression of HOTAIR. Furthermore, HOTAIR overexpression plasmids were transfected to SMMC-7721 and SK-Hep-1 cells. Additionally, MTT assay was used to evaluate the proliferation of transfected cells. The scratch and transwell assays were used to determine the migration and invasion ability of the cell. The protein levels were determined with Western blot. lncRNA HOTAIR was overexpressed in SMMC-7721 and SK-Hep-1 cells. Ginsenoside-Rg3 reduced the level of lncRNA HOTAIR. Overexpressed lncRNA HOTAIR offset ginsenoside-Rg3 inhibited proliferation, migration and invasion of HCC cells. Furthermore, ginsenoside-Rg3 decreased the expression of p-AKT, p-PI3K, matrix metalloproteinase-2 (MMP2) and matrix metalloproteinase-9 (MMP9), which was reversed after the treatment of HOTAIR. LncRNA HOTAIR was overexpressed in SMMC-7721 cells. Ginsenoside-Rg3 could reduce the expression of lncRNA HOTAIR, resulting in the inhibited cell proliferation, migration and invasion. Furthermore, ginsenoside-Rg3 inhibited cell proliferation and invasion ability through the PI3k/AKT pathway. Thus, ginsenoside-Rg3 might be a potential and effective treatment for HCC. Graphical Abstract: uf0001